Method for extracting lithium from waste glass powder by water leaching
By using water-impregnation process in waste glass powder combined with ball mill modification and thermal modification technology, the problem of environmental pollution and impurity separation difficulties caused by acid extraction of lithium in the prior art is solved, and an efficient, low-cost and environmentally friendly lithium recycling effect is achieved.
Patent Information
- Application Number
- CN202411967817.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The prior art requires the use of a large amount of acid when extracting lithium from waste glass, resulting in increased environmental pollution, increased cost and increased difficulty in separation of impurities, and decreased purity of lithium.
The water-impregnation process is combined with ball milling and thermal modification technology, and the auxiliary agent MCln is mixed with glass powder for ball milling and thermal modification, destroying the internal structure of the glass, improving its water-extraction lithium extraction rate, and reducing the accompanying leaching of impurities.
It realizes efficient, low-cost and environmentally friendly lithium recycling, significantly improves the extraction rate and purity of lithium, and simplifies the subsequent impurity separation steps.
Smart Images

Figure CN119753360A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid waste recycling, and in particular relates to a method for recovering lithium from waste glass powder. Background Art
[0002] With the transformation of the global energy structure and the rapid development of new energy vehicles, the demand for lithium resources is growing. As a light metal, lithium has become particularly important due to its key applications in battery technology. Traditional lithium resources mainly come from lithium ore and salt lake brine, but with the gradual depletion of resources and the increasing prominence of environmental problems, it has become urgent to find new sources of lithium resources.
[0003] Waste glass materials, especially glass products containing lithium, have become a potential lithium resource due to their widespread production and use. It is estimated that the amount of waste glass generated worldwide each year is as high as millions of tons, some of which contain a certain amount of lithium. However, most of these waste glasses are currently landfilled or recycled, and the lithium resources in them cannot be effectively recovered. Existing waste glass processing methods mainly focus on physical recycling, that is, crushing the glass for road construction, building materials, etc. These methods fail to make full use of the valuable elements in the glass, especially lithium.
[0004] In order to recycle lithium resources from waste glass powder, the prior art generally extracts by acid leaching, and a large amount of acid is required during the treatment process, causing environmental pollution. For example, a Chinese patent with publication number CN 116445735 A discloses a method for extracting metallic lithium from waste glass, wherein waste glass containing lithium is ground into glass powder, the glass powder is then processed with an abrasive, and calcined in a high-temperature furnace, the processed glass powder is mixed with an acid solution, the glass powder is contacted with hydrofluoric acid and perchloric acid for a first heating treatment, cooled, and water is added to the cooled product for a second heating treatment to obtain a glass dissolving solution, the prepared glass dissolving solution is washed and filtered, and finally lithium carbonate is extracted.
[0005] The Chinese patent document with publication number CN118813959A discloses a method for recovering valuable elements in lithium-containing glass waste, and specifically records a scheme for acid leaching lithium-containing glass waste. The Chinese patent document with publication number CN118497499A discloses a method for comprehensively recovering valuable components in lithium-containing glass powder, and also records a scheme for acid leaching lithium-containing glass powder. In addition, the Chinese patent document with publication number CN118207428A discloses a method for extracting lithium from lithium-containing silicon-alumina glass, and specifically records a scheme for mixing lithium-containing silicon-alumina glass, soluble M salt and sulfuric acid solution, leaching under pressure, and obtaining a filtrate and a filter residue after separation, wherein the filter residue contains aluminum alum precipitate, and the aluminum alum precipitate contains M, Al and sulfate.
[0006] In summary, when extracting lithium from waste glass, the prior art usually requires the use of a large amount of acid to leach lithium, which increases the cost of use and has a great impact on the environment. Acid leaching is also prone to leach impurity elements from glass powder, which increases the difficulty of subsequent impurity separation and reduces the purity of lithium carbonate. Therefore, developing a method for extracting lithium from waste glass powder by water leaching that is efficient, low-cost, environmentally friendly, and reduces the leaching of impurity elements is of great significance for alleviating the shortage of lithium resources, reducing the impact on the environment, and promoting the development of a circular economy. Summary of the invention
[0007] In view of the problems faced by the existing recycling of waste glass powder, the purpose of the present invention is to provide a method for recovering lithium from waste glass powder, aiming to provide a method with cheap reaction raw materials, short reaction process and efficient recovery of lithium in an acid-free system, and finally to produce lithium carbonate.
[0008] Li, silicon, Al and other components in the glass are highly fused at high temperature to form a dense fused phase. Compared with conventional minerals, the difficulty of leaching is significantly increased, and the leaching process adapted to conventional lithium ore is difficult to simply transfer to the extraction of lithium from glass. In view of the difficulty of extracting lithium from glass, the main existing means is acid leaching after roasting. Acid leaching will introduce more impurities into the glass, which will increase the difficulty and purity of subsequent lithium separation. In response to this problem, the present invention attempts to use a water leaching process to extract the lithium therein, but studies have shown that there are relatively few pretreatment methods in the prior art that can effectively adapt to the ultra-dense and hydrophobic characteristics of glass, which makes it difficult for the lithium component therein to achieve the expected water leaching extraction rate. In response to this problem, the present invention has conducted in-depth research and provides the following improvement scheme:
[0009] A method for recovering lithium from waste glass powder, comprising mixing lithium-containing waste glass powder and an additive for ball milling modification, and then thermally modifying at a temperature of 300 to 900° C. to obtain a thermally modified material;
[0010] The thermally modified material is subjected to water leaching treatment to obtain a lithium-rich water leaching solution;
[0011] The auxiliary agent comprises MCln, wherein the M is at least one of Ca, Fe, Mg and NH4; and the n is the valence of M.
[0012] The present invention innovatively adopts the auxiliary agent to participate in the ball milling modification and thermal modification of waste glass powder in situ. Based on the combination of the auxiliary agent, ball milling modification and mechanical modification, it can effectively break down the internal structure of the glass, optimize its surface physical and chemical properties, and thus effectively improve its water leaching lithium rate. In addition, it also helps to significantly reduce the accompanying leaching of impurities in the glass, thereby effectively reducing the difficulty of lithium extraction, separation and purification, and is conducive to obtaining high-quality lithium products.
[0013] In the present invention, the lithium-containing waste glass powder has an Al content of 20-30wt.%, a Si content of 40-50wt.%, a Li content of 1.0-10wt.%, a Mg content of 1-3wt.%, a Ca content of 0.5-2wt.%, a Na content of 0-2wt.%, and other trace elements such as Fe, Ni, Mn, Cr, Pb, Ti, etc., the contents of which are all less than 0.5wt.%, and the particle size is ≥100 mesh.
[0014] In the present invention, the MCln preferably contains NH4Cl, and more preferably contains CaCl2 and NH4Cl in a weight ratio of 0.5 to 2:1. Studies have shown that the preferred MCln can unexpectedly achieve synergy, and can obtain better efficiency and effect of lithium extraction from glass water at a lower processing temperature.
[0015] In the present invention, the auxiliary agent also includes an auxiliary agent, and the auxiliary agent includes at least one of calcium carbonate, calcium oxide, and magnesium carbonate. Studies have shown that the combination of the preferred MCln and the auxiliary agent can further improve the ball milling-heat dual modification effect of the glass, and help to further improve the lithium extraction efficiency and purity.
[0016] In the present invention, the content of MCln in the auxiliary agent is above 50wt.%, and can further be 50-70wt.%.
[0017] In the present invention, the weight ratio of the lithium-containing waste glass powder to the additive is 1:0.5-2; further, it can be 1:1-1.5.
[0018] In the present invention, the ball milling speed in the ball milling modification stage is 150 to 400 r / min, and can further be 300 to 350 r / min.
[0019] Preferably, the ball milling modification time is 0.5 to 5 hours, and further can be 1 to 3 hours.
[0020] In the present invention, the atmosphere for thermal modification is at least one of air, argon and nitrogen.
[0021] In the present invention, the heat treatment temperature is 700-900° C., wherein, under the preferred auxiliary agent, the heat treatment temperature can be reduced to 300-600° C., and further can be 350-450° C. Studies have shown that under the preferred auxiliary agent of the present invention, it helps to further optimize the ball milling-heat modification effect, and can further optimize the efficiency and effect of lithium extraction from glass water. In addition, it also helps to improve the purity of the prepared lithium product.
[0022] In the present invention, the holding time at the heat treatment temperature is 0.5 to 4 hours, and can further be 1 to 3 hours.
[0023] In the present invention, the liquid-to-solid ratio in the water immersion stage is 10 to 50:1 (ml / g), and can further be 15 to 25 (ml / g).
[0024] Preferably, the immersion time is 0.5 to 3 hours, and may further be 1 to 2 hours.
[0025] In the present invention, the lithium-rich water leaching solution is subjected to carbonization precipitation treatment to obtain lithium carbonate.
[0026] Beneficial Effects
[0027] In the present invention, part of the lithium oxide in the waste glass powder may be wrapped inside by silicon dioxide and aluminum oxide, and is highly fused, with a large surface hydrophobicity, and it is difficult to efficiently water-soak after heat treatment. In view of this problem, the present invention innovatively adopts an auxiliary agent to participate in its ball milling modification and thermal modification in situ, and the auxiliary agent is mixed with the glass powder for ball milling activation, so that the auxiliary agent can be better adhered to and contacted with the glass powder, and even penetrated into the surface cracks of the glass powder, which is beneficial to the subsequent thermal modification step. Based on the combination of auxiliary agent-ball milling modification and thermal modification, the fusion structure of the glass is effectively destroyed. In addition, its surface hydrophilicity is also improved, thereby effectively improving its subsequent water immersion effect, reducing the accompanying leaching of impurities in the glass, and being conducive to obtaining lithium products efficiently and with high purity. At the same time, when ammonium chloride is used as an auxiliary agent or mixed with other auxiliary agents for heat treatment, the heat treatment temperature can be reduced, and further, the impurity separation step before the subsequent water immersion step can be greatly reduced or even avoided, shortening the reaction process, and the auxiliary auxiliary agent can be further recycled. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the process flow chart of Example 1;
[0029] Figure 2 This is the XRD of the Li2CO3 sample regenerated in Example 1. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0031] The lithium-containing glass powder used in the following cases is recycled from glass cooking surfaces, car windshields and fireplace panels. For example, as an optional solution, the contents of the main components are: Al content 20-25wt.%, Si content 40-45wt.%, Li content 1.1-5.0wt.%, Mg content 1.3-1.5wt.%, Ca content 1-1.2wt.%, Na content 0.3-0.5wt.%, other trace elements such as Fe, Ni, Mn, Cr, Pb, Ti, etc. are all less than 0.5wt.%, and the particle size is ≥100 mesh.
[0032] Embodiment 1:
[0033] Step (1): crushing the waste lithium-containing glass powder, and then passing it through a 100-mesh sieve, collecting the sieved sample to obtain powder A. After testing, the lithium content in the powder A is 2.7%;
[0034] Step (2): the additive (comprising CaCl2 and auxiliary additive CaCO3 in a weight ratio of 1:1), the additive and powder A in a mass ratio of 2:2 are mixed in a ball milling jar, and then placed in a high-energy planetary ball mill, and ball milled at a speed of 300 r / min for 2 h to obtain a mixed ball milled material B;
[0035] Step (3): placing the mixed ball mill material B in a high temperature furnace in an air atmosphere for roasting, the roasting temperature is set to 850° C., the roasting time is 2 h, and a clinker C is obtained;
[0036] Step (4): subjecting the clinker C to water leaching at a liquid-to-solid ratio of 30:1 (ml / g), stirring at room temperature for 1 hour and then separating the solid and the liquid to obtain a lithium-containing leaching solution D with a lithium leaching rate of 98.7%;
[0037] Step (5): Add sodium carbonate as a precipitant to the lithium-containing leaching solution D, adjust the solution pH to 9-10, and then filter to remove Ca impurities. The filter residue is calcium carbonate, which can be further recovered and used as an auxiliary agent. The filtrate is then evaporated and concentrated to a solution E with a lithium concentration of 14.3 g / L. Sodium carbonate is added to the solution E for evaporation and crystallization. After filtration and washing, a lithium carbonate sample with a purity of 99.5% is obtained.
[0038] Example 2
[0039] Compared with Example 1, the only difference is that the type of auxiliary agent in step 2 and the roasting temperature and roasting time in step 3 are changed. Other operations such as the amount of auxiliary agent and other parameters are the same as in Example 1. The experimental groups are:
[0040] Group A: The auxiliary agents are FeCl3 and CaCO3 in a weight ratio of 1:1, the temperature is 800℃: the lithium leaching rate is 97.3%, and the purity of lithium carbonate is 99.2%.
[0041] Group B: The auxiliary agents are MgCl2 and CaCO3 in a weight ratio of 1:1, the temperature is 850℃, and the time is 1.5h: the lithium leaching rate is 98.4%, and the purity of lithium carbonate is 99.3%.
[0042] Group C: The auxiliary agents are NH4Cl and CaCO3 in a weight ratio of 1:1, the temperature is 350℃: the lithium leaching rate is 96.8%, and the purity of lithium carbonate is 99.9%.
[0043] Group D: The auxiliary agents are CaCl2, NH4Cl and CaCO3 in a weight ratio of 0.5:0.5:1, the temperature is 450℃: the liquid-to-solid ratio of water leaching is 20ml / g. The lithium leaching rate is 99.3% and the purity of lithium carbonate is 99.8%.
[0044] Group E: No auxiliary additives, only CaCl2, temperature 850℃: lithium leaching rate 87.3%, lithium carbonate purity 98.1%.
[0045] It can be seen from Examples 1 and 2 that the use of an additive containing MCln to perform ball milling-heat dual modification of glass can improve the lithium extraction efficiency and effect of the glass. In addition, on this basis, the use of MCln-auxiliary additive combination as an additive, especially the use of CaCl2-NH4Cl-auxiliary additive combination as an additive, can further improve the modification effect of the glass, which helps to further improve the lithium extraction rate and extraction purity of the glass.
[0046] Example 3
[0047] Compared with Example 1, the only difference is that in step 2, the weight ratio of the auxiliary agent to the powder A is 1.5:1, the ball mill speed is set to 350 r / min, and the ball milling time is set to 2.5 h: the lithium leaching rate is 99.4%, and the purity of lithium carbonate is 99.6%.
[0048] Example 4
[0049] Compared with Example 1, the only difference is that step 3 is roasted under argon atmosphere: the lithium leaching rate is 99.2%; the purity of lithium carbonate is 99.7%.
[0050] Example 5
[0051] Compared with Example 1, the only difference is that the auxiliary agent in step 2 is replaced by CaO, and the roasting temperature is set to 900° C.: the lithium leaching rate is 98.4%, and the purity of lithium carbonate is 99.4%.
[0052] Comparative Example 1:
[0053] Compared with Example 1, the only difference is that acid leaching is used instead of water leaching. Specifically, in step 4, the calcined product is acid-leached in 0.5M H2SO4 at a liquid-to-solid ratio of 30:1 (ml / g), and the solid-liquid separation is carried out after stirring at room temperature for 1 hour to obtain a lithium-containing leaching solution D, the lithium leaching rate is 98.8%, and the purity of the finally obtained lithium carbonate is 90.3%.
[0054] Comparative Example 2:
[0055] Compared with Example 1, the only difference is that in step 2, no auxiliary agent is added, and other operating conditions are the same as in Example 1. As a result, the lithium leaching rate is 5.8%.
[0056] Comparative Example 3:
[0057] Compared with Example 1, the only difference is that in step 2, no CaCl2 is added to the additive, only an auxiliary additive is included, and the total additive dosage and other operating conditions are the same as in Example 1. As a result, the lithium leaching rate is 33.1%.
[0058] Comparative Example 4:
[0059] Compared with Example 1, the only difference is that in the auxiliary agent, NaCl is used to replace CaCl2 by weight, the total auxiliary agent dosage and other operating conditions are the same as Example 1, and the results are that the lithium leaching rate is 75.8% and the purity of lithium carbonate is 96.3%.
[0060] Comparative Example 5:
[0061] Compared with Example 1, the only difference is that the auxiliary agent in step 2 is added in step 3, and the other operations and parameters are the same as those in Example 1: the lithium leaching rate is 72.2%, and the purity of lithium carbonate is 97.9%.
[0062] It can be seen from Examples 1 and 2 that the auxiliary agent of the present invention, especially comprising MCl n The combination of the auxiliary agent and the auxiliary agent can obtain an excellent effect of leaching lithium from glass water. In addition, by comparing Example 1 with Comparative Examples 1 to 5, it can be seen that the ball milling and thermal modification of the MCln in-situ parameter glass of the present invention can unexpectedly achieve synergy and improve the effect of leaching lithium from glass water.
Claims
1. A method for recovering lithium from waste glass powder, characterized in that: The lithium-containing waste glass powder and the additive are mixed and ball-milled for modification, and then thermally modified at a temperature of 300 to 900° C. to obtain a thermally modified material; The thermally modified material is subjected to water leaching treatment to obtain a lithium-rich water leaching solution; The auxiliary agent comprises MCln, wherein the M is at least one of Ca, Fe, Mg and NH4; and the n is the valence of M.
2. The method according to claim 1, characterized in that The lithium-containing waste glass powder has an Al content of 20-30wt.%, a Si content of 40-50wt.%, a Li content of 1.0-10wt.%, a Mg content of 1-3wt.%, a Ca content of 0.5-2wt.%, and a Na content of 0-2wt.%. The contents of other trace elements such as Fe, Ni, Mn, Cr, Pb, Ti, etc. are all less than 0.5wt.%, and the particle size is ≥100 mesh.
3. The method according to claim 1, characterized in that The MCln contains NH4Cl, preferably CaCl2 and NH4Cl in a weight ratio of 0.5 to 2:1; Preferably, the auxiliary agent further comprises an auxiliary auxiliary agent, and the auxiliary auxiliary agent comprises at least one of calcium carbonate, calcium oxide and magnesium carbonate.
4. The method according to claim 3, characterized in that In the auxiliary agent, the content of MCln is above 50wt.%.
5. The method according to claim 1, 3 or 4, characterized in that: The weight ratio of the lithium-containing waste glass powder to the additive is 1:0.5-2.
6. The method according to claim 1, characterized in that The ball milling speed in the ball milling modification stage is 150-400 r / min; Preferably, the ball milling modification time is 0.5 to 5 hours.
7. The method according to claim 1, characterized in that The atmosphere for thermal modification is at least one of air, argon and nitrogen.
8. The method according to claim 1, characterized in that The heat treatment temperature is 300-600°C.
9. The method according to claim 1, characterized in that The holding time at the heat treatment temperature is 0.5 to 4 hours; Preferably, the liquid-to-solid ratio in the water immersion stage is 10 to 50:1 (ml / g); Preferably, the immersion time is 0.5 to 3 hours.
10. The method according to claim 1, characterized in that The lithium-rich aqueous solution is subjected to carbonization precipitation treatment to obtain lithium carbonate.
Citation Information
Patent Citations
Method for preparing lithium carbonate by extracting lithium from lepidolite by adopting two-stage chloridizing roasting and alkali liquor leaching method
CN108118143A
Compound roasting auxiliary agent and application in lithium-containing dolomite modification
CN108239698A
Lithium extraction method for lithium-containing minerals
CN117070770A
Recovery method of waste lithium-aluminum-silicon microcrystalline glass
CN117222767A
Method for selectively separating lithium element from lithium-containing layered silicate mineral
CN117403075A